Inhibin B suppresses anoikis resistance and migration through the transforming growth factor‐β signaling pathway in nasopharyngeal carcinoma. Issue 11 (20th October 2018) - Zou, Guoying; Ren, Biqiong; Liu, Yi; Fu, Yin; Chen, Pan; Li, Xiayu; Luo, Shudi; He, Junyu; Gao, Ge; Zeng, Zhaoyang; Xiong, Wei; Li, Guiyuan; et al.
Abstract : Inhibin B (INHBB), a heterodimer of a common α‐subunit and a βB‐subunit, is a glycoprotein belonging to the transforming growth factor‐β (TGF‐β) family. In this study, we observed INHBB expression was reduced in nasopharyngeal carcinoma (NPC) tissues compared to non‐tumor nasopharyngeal epithelium tissues, and INHBB was associated with lymph node metastasis, stage of disease, and clinical progress. Positive expression of INHBB in NPC predicted a better prognosis (overall survival, P  =   0.038). However, the molecular mechanisms of INHBB have not been addressed in NPC. We induced anoikis‐resistant cells in NPC cell lines under anchorage‐independent conditions, then found epithelial‐mesenchymal transition markers changed, cell apoptosis decreased, cell cycle was modified, and invasion strengthened in anoikis‐resistant NPC cells. These anoikis‐resistant NPC cells showed decreased expression of INHBB compared with adhesion cells. Furthermore, INHBB was found to influence the above‐mentioned changes. In the anoikis‐resistant NPC cells with INHBB overexpression, apoptotic cells increased, S phase cells weakened, vimentin, matrix metallopeptidase‐9, and vascular endothelial growth factor A expression were downregulated, and E‐cadherin expression was upregulated, and vice versa in knockdown of INHBB (INHBB shRNA) anoikis‐resistant NPC cells. Diminished INHBB expression could activate the TGF‐β pathway to phosphorylate Smad2/3 and form complexes in the nucleus, which resulted in the above changes. Thus, our results revealed for the first time that INHBB could suppress anoikis resistance and migration of NPC cells by the TGF‐β signaling pathway, decrease p53 overexpression, and could serve as a potential biomarker for NPC metastasis and prognosis as well as a therapeutic application. Abstract : Our results showed for the first time that inhibin B could suppress anoikis resistance and migration of nasopharyngeal carcinoma cells by the transforming growth factor‐β signaling pathway, and decrease p53 overexpression. Inhibin B could serve as a potential biomarker for nasopharyngeal carcinoma metastasis and prognosis, as well as a therapeutic application.